Effect of external auditors’ attributes on financial reporting quality of listed insurance firms in Nigeria - Aruwa, Suleiman A.S.; Naburgi, Musa M; Okwa, Ene Iyana (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
Purpose: The need for greater attention to the activities of insurance firms, as bankruptcy would not just affect the shareholders, customers, and employees alone but the economy in general. This study assessed the effect of audit attributes on the financial reporting quality of listed insurance firms in Nigeria. Methodology: The sample of the study is 20 insurance firms listed in the Nigerian Exchange Group (NGX) out of the 23 insurance firms. The data for this study were secondary data sources, which were collected from published financial statements of the selected listed insurance firms for the period of 10 years, covering 2013-2022. Results and conclusion: The study found that audit independence has a negative and insignificant effect on financial reporting quality. Also, the study found that audit competence has a positive and significant effect on financial reporting quality. The study concluded that the competence of auditors shows a positive significant effect on financial reporting quality; this indicates that competence is one of the factors that influence financial reporting quality even when not supported by other factors to effectively enhance FRQ. Implication of findings: Based on the findings, the study recommended that regular training and certification programs should be organized for auditors to ensure they possess the necessary skills and knowledge, supported by strong regulatory oversight. Professional accounting bodies and regulators should collaborate to offer continuous professional development programs.